Advances in mergers and acquisitions. Vol. 8 - Finkelstein, Sydney; Cooper, Cary L. (Emerald, 2009)
What makes the Advances in Mergers and Acquisitions series stand out is its focus on all three characteristics that make up this research field - studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad, and inclusive, approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The collections published each year provide cutting edge ideas by leading scholars on a global scale. Doing so not only broadens the questions being studied, but also helps researchers consider the inter-relationships among different perspectives. In the final analysis, the best way to build understanding around a topic as diffuse as mergers and acquisitions is to be both integrative, and expansive, in choice of research questions and theoretical underpinnings. Advances in Mergers and Acquisitions offers this unique perspective, not easily found elsewhere, that will help scholars think about mergers and acquisitions in new ways, building our knowledge base on this critical topic.
Keywords: Consolidation and merger of corporations.; Consolidation and merger of corporations -- Management.; elektronické knihy; electronic books